Evaluasi Usability dan Rekomendasi Perbaikan Website SIP Bro Menggunakan Metode SUS Dan Think Aloud - Naila, Tia Cahyani; Wahyuni, Evi Dwi; Rahmayanti, Vinna (P3M Politeknik Negeri Banjarmasin, 2023)
In terms of governance, websites have a strategic function as tools that support government activities, where their existence plays a role in digital engagement with the public. One of the government agencies in Blora City, namely the Regional Development and Planning Agency (BAPPEDA), has utilized and implemented an administrative website in the field of research and development, called SIP Bro. Based on observations, after the implementation of the SIP Bro website, there are still issues or weaknesses identified. So far, there have been no efforts to conduct a minimum evaluation to assess its Usability and whether the intended goals are achieved. Therefore, this study aims to determine the Usability analysis scores of the SIP Bro website using the System usability scale method. To further enhance the effectiveness of evaluating and developing the SIP Bro website, this research also incorporates the Think Aloud approach. The research findings conclude that the Usability score of the SIP Bro website obtained a score of 61.071, which falls under the